The Role of Children in Bridging the Technological Gap of Parents: A Social Philosophy Perspective in the Digital Era - Juliana, Revita; Anshori, Isa (Faculty of Social Science, Universitas Negeri Semarang, 2023)
The rapid advancement of technology has influenced various aspects of social life, particularly within the family environment. The current technological progress has resulted in a significant technological gap among the older generation, primarily due to generational differences between parents and children. These differences in generations lead to disparities in understanding and knowledge of technology. The consequences of this technological gap profoundly impact daily life patterns, often resulting in negative consequences. This technological gap can impact parental relationships, as parents with limitations in understanding technology often require their children's guidance. This is crucial because children tend to grow and adapt quickly to a world dominated by various advanced technologies. The primary objective of this study is to gain a comprehensive understanding of how children address the technology gap with their parents. The research methodology employed for this study is qualitative. In the process of data collection, participants were selected from families with school-age children possessing proficiency in using technology, while the parents needed more experience with modern technology. The findings of the research highlight the pivotal role that children play in enhancing the quality of life for their parents in addressing technological disparities. Children serve as valuable sources of knowledge, guiding their parents in learning and using technology effectively.